Mind Over Market: Behavioural Determinants of Renewable Energy Investment Adoption in India - Sharma, Sudarshana; Gaikwad, Shubhangi V.; Raghuwanshi, Sandeep; Sikarwar, Priyanka; Agarwal, Reetika; Verma, Deepti (International Journal of Energy Economics and Policy, 2025)
This study investigates the psychological and behavioural drivers affecting the adoption of renewable energy investments in India, a rapidly developing nation with urgent energy transition targets. Despite technological and financial incentives, adoption remains minimal, necessitating an exploration of the cognitive and dispositional factors influencing human investment intentions. A structured questionnaire was distributed to 416 urban participants in Tier-I and Tier-II Indian cities. Metrics including cognitive biases, behavioural inertia, gain/loss framing, personality factors, and green behavioural spillover were assessed utilising validated scales. The data were analysed using Structural Equation Modelling (SEM) in IBM AMOS, which facilitated the evaluation of both the measurement models for understanding the behavioural determinants of renewable energy investment adoption. The findings indicated that all five behavioural characteristics had a substantial impact on plans to invest in renewable energy. Green behavioural spillover revealed as the most significant predictor, succeeded by cognitive biases and personality characteristics. The model explained 67% of the variance in investment intentions, underscoring the significance of behavioural factors in renewable energy transitions. This paper proposes an innovative behavioural framework specific to India, addressing deficiencies in current techno-economic adoption models. The results provide practical guidance for developing behavioural treatments, focused awareness campaigns, and policy instruments that correspond with psychological motivators, so improving the efficacy of renewable energy adoption methods.